Adoption Of Agricultural Technology Innovation In Indonesia: Challenges And Alternative Solutions - Filya Hidayati; Rahmat Syahni; Irfan Suliansyah; Hery Bachrizal Tanjung (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpose: The adoption of agricultural innovations in Indonesia faces numerous challenges. However, with appropriate approaches, there is significant potential to improve both productivity and the welfare of farmers. This paper aims to analyze the key determinants influencing farmers’ acceptance of new technologies or innovations, as well as the factors that may accelerate their adoption. Methodology: This study employs a literature review approach, analyzing various sources including academic journals, reports, and statistical data related to innovation adoption theories and farmers' behavioral patterns. Results: The study identifies a complex interplay of factors that hinder the adoption of agricultural innovations among Indonesian farmers. Key barriers include limited access to relevant information, low digital literacy, high financial costs, mismatch between innovation characteristics and local conditions, inadequate agricultural extension services, and farmers’ dependence on traditional markets. Additionally, institutional weaknesses—such as poor coordination among government bodies, ineffective policies, limited infrastructure, and the exclusion of farmers from participatory processes—further exacerbate adoption challenges. These findings emphasize that technological solutions alone are insufficient; addressing adoption gaps requires systemic improvements in policy, support services, and farmer engagement. Findings: Reveals significant outcomes from the research that contribute new insights to the field of study. This can include innovations, discoveries, or previously unknown information. Novelty: This research introduces a comprehensive, multi-dimensional framework for understanding the barriers to agricultural innovation adoption in Indonesia by integrating technological, socio-economic, and institutional factors, rather than examining them in isolation. Originality: The study uniquely contributes to existing literature by synthesizing recent empirical evidence and theoretical insights to highlight context-specific challenges faced by Indonesian farmers, and by proposing actionable, collaborative strategies that link innovation design with local socio-cultural realities and policy reform—an approach rarely explored in previous studies on agricultural technology adoption. Conclusion: Addressing the challenges of agricultural innovation adoption requires collaborative efforts among stakeholders. Strategies should focus on improving access to information, providing financial support, tailoring innovations to local conditions, strengthening the role of agricultural extension agents, increasing farmer motivation, and developing partnerships and market access.